2006
DOI: 10.1159/000094589
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use before By-Pass Surgery Decreases the Incidence and Shortens the Duration of Postoperative Atrial Fibrillation

Abstract: Backround: The aim of the present observational study is to search the incidence of postoperative atrial fibrillation (AF) in patients with or without preoperative statin treatment. Methods andResults: The population consisted of 362 consecutive patients (267 on and 95 not on statin). Diabetes mellitus was more frequent in statin group (p = 0.03). Other demographic and procedural variables were similar in the both groups (All p > 0.05). Postoperative AF was less frequent and its duration was shorter in statin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 33 publications
0
58
0
1
Order By: Relevance
“…Regarding the effects of ACE inhibitors or AT 1 -blockers in the prevention of postsurgery AF, no randomized studies have been published. Finally, it has been suggested that POAF was less frequent and its duration shorter in patients treated with statins in comparison with a nonstatin group, 56,57 and associated with a decrease in inflammatory markers.…”
mentioning
confidence: 99%
“…Regarding the effects of ACE inhibitors or AT 1 -blockers in the prevention of postsurgery AF, no randomized studies have been published. Finally, it has been suggested that POAF was less frequent and its duration shorter in patients treated with statins in comparison with a nonstatin group, 56,57 and associated with a decrease in inflammatory markers.…”
mentioning
confidence: 99%
“…Both cardiac surgery and heart failure activate RAS (17) which in turn may induce electrical and structural remodeling (8,16). Structural and electrical remodeling may initiate and perpetuate postoperative AF (18). Aldosterone has parasympathetic (19,20) and sympathetic (15) effects, both of which may cause AF (21).…”
Section: Discussionmentioning
confidence: 99%
“…Statins, which have anti-inflammatory actions, have been shown to be effective in preventing AF in different patient populations (4)(5)(6)(7)(8)(9), including recurrence of AF after electrical cardioversion (EC) (10,11). N-3 polyunsaturated fatty acids (PUFAs) also have anti-inflammatory actions (12).…”
Section: Introductionmentioning
confidence: 99%